Anti-Inflammatory Potential of 3-Hydroxy-β-Ionone from Moringa oleifera: Decreased Transendothelial Migration of Monocytes Through an Inflamed Human Endothelial Cell Monolayer by Inhibiting the IκB-α/NF-κB Signaling Pathway - Thitiya Luetragoon; Krai Daowtak; Yordhathai Thongsri; Pachuen Potup; Philip C. Calder; Kanchana Usuwanthim (Molecules)
Moringa leaves provide numerous health benefits due to their anti-inflammatory properties. This study presents the first evidence that endothelial cell inflammation can potentially be ameliorated by moringa leaf extract. Here, we established an experimental human blood vessel cell model of inflammation using EA.hy926 cells. TNF-α was added after pre-treating the cells with crude leaf extract from Moringa oleifera Lam., a constituent fraction of the extract, and the bioactive component 3-hydroxy-β-ionone. The extract and the active ingredient significantly decreased the levels of pro-inflammatory mediators such as IL-6, IL-8, and MCP-1; decreased IκB-α and NF-κB p65 phosphorylation; and decreased the expression of VCAM-1, PECAM-1, and ICAM-1, three significant adhesion molecules. Furthermore, they attenuated THP-1 monocyte adhesion to the EA.hy926 monolayer and decreased monocyte transmigration across the monolayer. These findings suggest that 3-hydroxy-β-ionone and moringa leaf extract have anti-inflammatory properties and can be used as therapeutic agents to reduce the progression of diseases involving the inflamed endothelium by decreasing the production of inflammatory cytokines, chemokines, and adhesion molecules. This is promising for conditions such as atherosclerosis and neuroinflammation.